Towards A Decolonial Latin America: Identity, Difference and Solidarity in Augusto Monterroso’s (Very) Short Prose - Bell, Lucy (Revista Canadiense de Estudios Hispánicos, 2023)
Fragmentary and modest, Augusto Monterroso’s work has not received the same attention as that of his friends Juan Rulfo and Julio Cortázar. Yet his writing offers original perspectives on major cultural issues that remain relevant to the present day, including that of Latin American identity and difference. Engaging with Mignolo’s decolonial theory and Moreiras’s critique of regionalism through close readings Monterroso’s short prose (1959-98), this paper argues that it is precisely the use of a fragmentary aesthetics that allows Monterroso to anticipate the politics of (de)coloniality and representation that would only come to crystallize in academia in the twenty-first century.